A rare case of intradural extramedullary epidermoid with focal diastematomyelia - Harsh Deo Pandey; Avdhesh Shukla; Vivek Kankane; Avinash Sharma; Sridham Sutradhar (Asian Journal of Medical Sciences, 2024)
Diastematomyelia is a rare congenital deformity, more common in females usually associated with cutaneous manifestation of spinal dysraphism with congenital scoliosis. We report a female patient 26 years old with scoliosis in the dorsolumbar spine with dorsolumbar focal diastematomyelia type-2 with intradural extramedullary epidermoid which is a rare entity.